SDL and Technology: Implications for Adult Education - Ramona T. Sharpe; Tamara L. Kelley (Adult Education Research Conference, 2014)
As SDL is embraced and technology continually advances in organizations, new and improved skills and learning strategies will be required. This session will explore the anticipated change necessary for adult educators and related scholarly practitioners to be able to effectively support the learners in their organizations.